Subsidizing resilience: Evaluating Kenya's fertilizer subsidy program amid global supply chain disruptions - Ayalew, Hailemariam; Breisinger, Clemens; Karugia, Joseph T.; Kimaiyo, Faith Chepkemoi; Kimathi, Sally; Olwande, John (International Food Policy Research Institute, 2024)
Amid global supply chain disruptions and an escalating fertilizer crisis, Kenya’s National Fertilizer Subsidy Program (NFSP) emerges as a critical intervention to enhance agricultural resilience. This paper investigates the NFSP's impacts on fertilizer adoption, maize productivity, and market dynamics, employing a quasi-experimental design with two-way fixed effects and two-stage least squares (2SLS) estimation. We leverage random variation in government-issued SMS notifications to identify causal effects. Results show that the NFSP increased fertilizer adoption by 7%, leading to maize yield gains of 26–37% (164–233.5 kg/acre), with greater benefits for younger and more educated farmers. However, the program caused a substantial crowding-out effect, reducing private-sector fertilizer use by 49–57%. Barriers such as financial constraints, delayed notifications, and logistical inefficiencies limited equitable access, undermining the program's potential. Despite these challenges, the NFSP was cost-effective, offering favorable value-cost ratios for farmers and the government. To enhance impact and sustainability, we recommend addressing participation barriers and integrating private-sector agro-dealers into the distribution framework. This study provides crucial insights for policymakers on designing subsidy programs that balance immediate productivity gains with market sustainability, especially during periods of global agricultural uncertainty.